Penerapan Wireless Distribution System (WDS) Mesh Untuk Optimasi Cakupan Area Wi-Fi di UM Jember - Achmad Riyadus Sholikhin; Taufiq Timur Warisaji; Triawan Adi Cahyanto (Puslitbang Sinergis Asa Professional, 2020)
One very rapid change in computer networks is the use of Wireless Local Area Network (WLAN) to access systems both locally and the internet. One way to add an Access Point (AP) so as not to change the configuration of the running software is use the Wireless Distribution System Mesh (WDS) network. The use of WDS mesh at Universitas Muhammmadiyah Jember (UM Jember) enables a slightly different wireless configuration to reduce the connection loss in the user due to the wireless network area coverage. One step is use AP devices into one unit to handle the case of a connection break by utilizing a network service that is WDS Mesh. WDS Mesh can cover Wi-Fi areas at UM Jember, and the results of testing and analysis of client devices for APs that have been configured WDS Mesh with parameters Signal Strength, CCQ, Signal to Noise Ratio Ratio, Throughput is Excellent.